Effect of The Temperature on The Size of Inhibition Zone of the Clindamycin, Levofloxacin, Tetracycline, and Trimethoprim Activity Against Staphylococcus aureus ATCC 25923 - Sistiyono, Sistiyono; Martsiningsih, Marta Atik; Kasiyati, Menik; Rahayu, Muji; Pudyastuti, Rita Rena; Suyana, Suyana; Rahmawati, Ully; Rahmad; Faruq, Zulfikar Husni; Setiawan, Budi (JURNAL INFO KESEHATAN, 2024)
Antibiotic sensitivity testing is essential for determining bacterial susceptibility to antibiotics. In disc diffusion testing, several technical factors influence the diameter of the inhibition zone, including incubation temperature, which must be carefully controlled to ensure the validity of test results. This study aims to determine the mean, difference, and analyze the diameter of the inhibition zone of the antibiotics, namely Clindamycin, Levofloxacin, Tetracycline, and Trimethoprim against Staphylococcus aureus on Mueller-Hinton agar media with incubation temperatures of 33°C, 34°C, 35°C, 36°C and 37°C for 18 hours. This research is observational, with a cross-sectional design. The primary data is 100 data on the diameter of the antibiotic inhibition zone, obtained by measuring the diameter of the inhibition zone with different incubation temperatures. The selection of antibiotics is based on the mechanism of action of antibiotics inhibiting bacteria, namely the cell wall or cell membrane that surrounds the bacterial cell; the pieces of machinery that make the nucleic acids DNA and RNA, and the machinery that produces proteins (the ribosome and associated proteins) with a range of inhibition zones based on Internal Quality Control CLSI. The data and the repeated measure statistical test will be processed univariately to determine the significance of the difference in the diameter of the formed inhibition zone using the ANOVA test. The measurement of the inhibition zone diameter on the incubation temperature variation showed a significant difference with a p-value of 0.000 for Levofloxacin, Tetracycline, and Trimethoprim, while the p-value of Clindamycin is 0.010. For the other antibiotics, Levofloxacin, Tetracycline, and Trimethoprim antibiotics, the higher the incubation temperature, the average diameter of the inhibition zone is condensed, while for Clindamycin the higher the incubation temperature, the higher the average diameter of the inhibition zone is the same. Incubation temperature and volume affect the diameter of the antibiotic inhibition zone in the disc diffusion method for the antibiotic sensitivity test. It can be concluded that incubation temperature affects the diameter of the antibiotic inhibition zone in disc diffusion tests. It is recommended for future standardized and precise testing conditions to ensure accurate and reliable antibiotic sensitivity results.